Managing childcare and work responsibilities : the strategies of married women primary and infant headteachers - Evetts, Julia [Verfasser] (My University, 1988)
"The article analyses the strategies that had been developed by women teachers to enable them to meet their family obligations to care for young children and, at the same time, develop their teaching careers. Using career history data from a sample of twenty- five women headteachers, from a midlands county in England, the article considers the expectations these women had set themselves with regard to certain childcare tasks and how the had managed the resources they had, in order to meet these expectations. The interview data revealed that relationship, particularly between other women teachers, were an important resource in enabling these women to fulfil their childcare expectations while pursuing their teaching career." (author's abstract) ((en)) Welche Strategien entwickeln Lehrerinnen, um ihre Familienpflichten erfüllen und gleichzeitig ihre berufliche Karriere vorantreiben zu können? Dieser Frage geht der Artikel anhand der Daten aus einer Berufsverlaufsuntersuchung bei 25 Lehrerinnen aus einer mittelenglischen Grafschaft nach. Die Interviews mit diesen Frauen haben gezeigt, der vor allem zwischenmenschliche Beziehungen insbesondere zu anderen Lehrerinnen, es ihnen ermöglicht haben, ihren eigenen Ansprüchen an die Kinderbetreuung zu genügen und gleichzeitig ihre Karrierepläne als Lehrerinnen zu verfolgen. (IAB2)
Kindererziehung und Arbeitsverantwortung. Die Strategien verheirateter Lehrerinnen
Keywords: P 3.2.3 Lehrer; P 1.3 Frauen; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.4.4 Biografiegestaltung; Beruf und Familie; Frauen; Lehrer; Grundschule; Doppelrolle; Berufserfolg; Frauen in Einzelberufen; Frauenarbeit; Berufsproblem